Foreign direct investment, development and the new global economic order : a policy brief for the South (South Centre GenevaCH, 1997)
Analyses foreign direct investment (FDI) and the policy isues this raises for developing countries. Seeks to assist developing countries to assess their individual and collective policy stand with regard to the current drive for a global regime to establish free flow of FDI.
DC